A Consideration of Public Archaeology Theories. (2nd January 2016) - Matsuda, Akira
Abstract : It is possible to identify four approaches to public archaeology: educational, public relations, pluralist, and critical. The most significant divide in the discourse of public archaeology over the last few decades has existed between the educational and public relations approaches on one side, and the pluralist and critical approaches on the other. Today, however, the dividing line in these four approaches is gradually shifting, as the pluralist and critical approaches, which have so far tended to be grouped together as a more theoretical and post-processual category, are progressively splitting apart. What is emerging, as a result, is a new divide between the educational, public relations, and pluralist approaches on the one side, and the critical approach on the other. This shift seems to be caused by economic neo-liberalism which demands that archaeology be more viable in economic terms. The more archaeology seeks economic viability, however, the more it alienates itself from critical reflection. The critical approach is, thus, faced with the danger of being regarded as a detriment to the sustainability of archaeology. What seems to be crucially needed today, then, is to reconfigure public archaeology, so that it can cope with the presently dominant economic paradigm, while at the same time continuing to keep critiquing it.